Wybrane problemy efektywności wykorzystania kapitału ludzkiego na przykładzie przedsiębiorstw województwa zachodniopomorskiego - Czerniachowicz, Barbara (Chosen Problems of Efficiency the Useing of the Human Capital on Example of the Enterprises of Zachodniopomorskie Province, 2005)
The article presents the actual state of human capital management in big companies of the West Pomeranian Voivodship. In these research main barriers of carrying on personnel politics in analysed firms and showed problems concerning the development of human capital, building the knowledge and an intellectual capital of organisation. These kinds of resources, which belong to nonmaterial ones, decide about value of the whole enterprise and increased competition among companies. The author has analysed possibilities of application of statistical methods in the research on adjustment of work potential to commercial entities' needs
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 57-67